Maternal Health, Health Care Access, Information Access, Technology - Byamukama, Eliab Mpora; Komuhangi, Jacinta; Miganda, Vicent; Turyahebwa, Abanis (East African Journal of Business and Economics, 2024)
The study examined access to credit and the performance of small and medium enterprises in Bushenyi District, Uganda. The study was guided by the following objectives: to examine the extent of access to credit and the performance of small and medium enterprises in Bushenyi District. SMEs have been seen as uncommon supporters of the Ugandan economy because they both organize and work for innovative considerations. In any case, their execution and development are regularly ruined by different challenges. For the methodology, surveys and interviews were utilized to gather essential information, whereas diaries, books, and the web were sources of auxiliary information. The information was secured over five years, extending from the year 2019 to 2024. The relapse show has an R of 0.724, which shows a solid positive relationship between the factors. The coefficient of assurance, R square, demonstrates how well the information fits within the measurable range and how effective the fit is in clarifying the variety of the information. In this study, 52.4% of the variance within the dependent variable is explained by the independent factors, supporting financial services that are more inclusive and sensitive to SMEs. The areas of the study were challenged by the barriers and constraints facing SMEs in accessing credit from credit facilities. It was also limited to accessing the respondents since they were located across the Bushenyi District. Through creating an empowering environment for SMEs, the bridge that exists between huge and small companies can be limited. This may also be accomplished through segmenting NSE for SMEs posting and defining the administrative system that's inviting SMEs.